2008
DOI: 10.1186/1471-2407-8-384
|View full text |Cite
|
Sign up to set email alerts
|

Expression of centromere protein F (CENP-F) associated with higher FDG uptake on PET/CT, detected by cDNA microarray, predicts high-risk patients with primary breast cancer

Abstract: BackgroundHigher standardized uptake value (SUV) detected by 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) correlates with proliferation of primary breast cancer. The purpose of this study is to identify specific molecules upregulated in primary breast cancers with a high SUV and to examine their clinical significance.MethodsWe compared mRNA expression profiles between 14 tumors with low SUVs and 24 tumors with high SUVs by cDNA microarray. We identified centromere protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…[17][18][19][20]. We subsequently excluded five articles because of insufficient data (20)(21)(22)(23)(24), and four because of patient overlap (19,(25)(26)(27). Thus, we selected 85 articles for our review (14)(15)(16)(17)(18), representing 81 unique patient populations, totaling Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20]. We subsequently excluded five articles because of insufficient data (20)(21)(22)(23)(24), and four because of patient overlap (19,(25)(26)(27). Thus, we selected 85 articles for our review (14)(15)(16)(17)(18), representing 81 unique patient populations, totaling Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…By means of cDNA microarray and immunohistochemistry, we previously reported that expression levels of cellcycle-related proteins (Ki67 and CENP-F) were increased in tumors showing high FDG uptake in comparison with tumors showing low FDG uptake, suggesting that the level of FDG uptake could be explained, at least in part by the early stage proliferative activity of breast cancer cells [19].…”
Section: Introductionmentioning
confidence: 98%
“…Tumor glucose metabolism using FDG PET has the potential to distinguish viable cancer cells from those in suspension or necrotic components because the degree of tumor FDG uptake is closely associated with its proliferative activity [17]. Therefore, FDG PET could help to individualize treatment and to avoid potentially ineffective chemotherapies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%